Regorafenib Prior to Selective Internal Radiation Therapy Using 90Y-Resin Microspheres for Refractory Metastatic Colorectal Cancer Liver Metastases: Analysis of Safety, Dosimetry, and Molecular Markers - Kennedy, Andrew; Shipley, Dianna; Shpak, Max; Blakely, Laura; Hemphill, Brian; Shih, Kent; Lane, Cassie; Zimmerman, Lisa; McKenzie, Andrew; Mainwaring, Mark; Peyton, James D.; Zubkus, John; et al. (Frontiers in Oncology, 2019)
Background: This Phase II, open-label, study examined the safety of regorafenib followed by selective internal radiation therapy (SIRT) with regorafenib re-initiation in the treatment of metastatic colorectal cancer (mCRC) patients with liver metastases who are not surgical candidates. Methods: Patients received 160 mg regorafenib daily on a 21-day course followed by a 1 week washout prior to SIRT. Liver function was evaluated at 2 and 4 weeks after SIRT, and regorafenib re-initiated if liver function was normal. Patients were evaluated for safety, and restaged at weeks 6 and 12 following SIRT. In addition, protein and cytokine assays of blood were performed to identify candidate molecular biomarkers associated with outcomes. Individual patient voxel-based dosimetry assessment was performed post-SIRT. Results: Twenty-Five patients were enrolled and received a median 11 weeks regorafenib. Three patients received regorafenib, but not SIRT due to disease progression. The remaining 22 patients received SIRT with a median activity delivered to the liver of 38 mCi, mean normal liver dose of 14.98 Gy and tumor mean dose of 29.0 Gy with a tumor to normal ratio mean of 2.42. There were four treatment-related serious AEs and no treatment-related deaths. Median progression-free survival was 3.7 months and the median overall survival was 12.1 months. The relative densities of several biomolecules changed significantly during the course of treatment, most notably post-treatment increases in levels of sex-hormone binding globulin (SHBG) and decreased levels of the cytokine MIG (CXL9). Decreases in von Willebrand factor (VWF), the ankyrin repeat domain (ANKRD26), and MIG were associated with improved survival times. Post-treatment increases in alpha-2-macroglobulin (A2M) and the cytokine intercellular adhesion molecule (ICAM-1) were associated with reduced overall survival time, while increases in Eotaxin (CCL14) predicted longer overall survival times. Conclusions: The treatment of mCRC patients with liver metastases using regorafenib followed by SIRT was tolerable in this patient population. Further efficacy analysis of this treatment schema and analysis of potential molecular biomarkers using larger sample sizes is merited.